PERLINDUNGAN HUKUM ATAS KARYA DESAIN INDUSTRI KREATIF DITINJAU DARI PERSYARATAN KEBARUAN MENURUT UNDANG UNDANG NOMOR 31 TAHUN 2000 - Wiwaha Kusuma Brahmanda, Ida Bagus Komang (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
Indonesia since signed the Agreement on Trade Related Aspects of IntellectualProperty Rights (TRIPs agreement), nowadays Indonesia has the legal protection ofIntellectual Property Rights (IPR) internationally. After Indonesia has such regulations, theGovernment began to pay a serious attention from all forms of IPR and also to the arts andculture native to Indonesia. Since its development widely reported that Indonesia's IPRclaimed by Malaysia.
Keywords: intellectual property laws, legal protection, offense of fraud, claims